2016
DOI: 10.1097/ccm.0000000000001661
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Development and Evaluation of a Hemodynamic Critical Care Ultrasound: A Systematic Review of the Literature

Abstract: Assessment of cardiac function and volume assessment is becoming an essential skill in critical care medicine. Physicians can be taught bedside echocardiography in a time-effective manner with positive benefit to patients by applying a concise curriculum with limited content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 28 publications
1
23
0
2
Order By: Relevance
“…A focused training program may help to achieve proficiency in bedside echocardiography [42]. A systematic review analyzed studies assessing the competence of residents with respect to bedside echocardiography after focused training in the intensive care unit [43]. Residents were involved in theoretical sessions integrating didactics and interactive clinical cases and hands-on teaching.…”
Section: Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…A focused training program may help to achieve proficiency in bedside echocardiography [42]. A systematic review analyzed studies assessing the competence of residents with respect to bedside echocardiography after focused training in the intensive care unit [43]. Residents were involved in theoretical sessions integrating didactics and interactive clinical cases and hands-on teaching.…”
Section: Trainingmentioning
confidence: 99%
“…In most studies competence was defined as the ability to both acquire and interpret images correctly. Kanji et al [43] suggested that a minimum of 30 independent examinations is recommended to develop an acceptable level of competence with respect to answering binary questions regarding biventricular function, pericardial effusion, and volume status.…”
Section: Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 This workshop format has been published by several institutional courses for trainees as well. [21][22][23] These approaches tend to be "teacher-centric" models, whereby it is easier for a small number of faculty to teach a larger number of learners. 24 However, this may not equate to students fully learning the material, as is the focus in more learner-centric models.…”
Section: Introductionmentioning
confidence: 99%
“…Several ultrasound protocols have been developed to assist in the assessment of shock and respiratory distress , incorporating examinations of the heart, lungs and abdomen, in addition to other organ systems. Ultrasound has been shown to improve diagnostic accuracy, change management and may reduce mortality rates for critically ill patients. Although there have been several studies demonstrating the feasibility of ultrasound training in LMICs , evidence on the impact of ultrasound on emergency care in such settings is limited .…”
Section: Introductionmentioning
confidence: 99%